PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE CO-OP CO-OP TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PADA PESERTA DIDIK KELAS VII SMP NEGERI 2 DAMPAL SELATAN - Kahar, Moh Jusri; Fitri, Liza (Scolae: Journal of Pedagogy, 2023)
The purpose of this study was to determine whether there was a positive effect of the Co-Op Co-Op type of Cooperative Learning Model on the mathematical communication skills of the students of SMP Negeri 2 Dampal Selatan. This research is a type of Pre Experimental Design research. The population and sample in this study were all seventh grade junior high school students. The instrument used to collect data was a mathematical communication ability test which was carried out before being treated (pretest) and after being treated (posttest) as well as observing the learning implementation sheet. Where the results of data analysis show that Ho is rejected, that is, there is an influence. The data analysis of this research is descriptive statistical analysis and inferential statistical analysis. Hypothesis testing using the i one sample test. Based on the results of the study, it can be concluded that there is a positive effect of the Co-Op Co-Op type of Cooperative Learning Model on the Mathematical Communication Ability of the seventh grade students of SMP Negeri 2 Dampal Selatan (medium category).